Bat Coronavirus of Pteropus alecto from Gorontalo Province, Indonesia - Wenty Dwi Febriani; Uus Saepuloh; Ellis Dwi Ayuningsih; R. Suryo Saputra; Azhari Purbatrapsila; Meis Jacinta Nangoy; Tiltje Andretha Ransaleh; Indyah Wahyuni; Safriyanto Dako; Rachmitasari Noviana; Diah Iskandriati; Ligaya ITA Tumbelaka; Joko Pamungkas (The Faculty of Veterinary Medicine of Syiah Kuala University, 2018)
Bats have been known as natural reservoirs for potential emerging infectious viruses, such as Lyssaviruses, Coronaviruses, Ebola viruses, Nipah virus, and many others. Because of their abudance in population, wide distribution and mobility, bats have a greater risk as source for zoonotic transmission than other animals. Despite the facts of their role as reservoirs for many pathogens, not until an epidemic of Severe Acute Respiratory Coronavirus (SARS-CoV) in 2003 and Middle-East Respiratory Syndrome Coronavirus (MERS-CoV) in 2012, that people pay much attention about coronavirus in bats. SARS-like virus also found in bats with a higher prevalence rate. This study aims to detect the coronavirus of bats in Gorontalo province Indonesia, characterization at the molecular level of the coronavirus genome and determining the level of kinship (through trees filogenetic). This study was conducted as part of bigger PREDICT Indonesia project, in particular to examine coronavirus in bats from Gorontalo province, Indonesia. As many as 95 rectal swab samples collected from flying foxes (Pteropus alecto) were analyzed in the laboratory using Consensus Polymerase Chain Reaction (PCR) technique to amplify the target sequence from RNA-dependent RNA Polymerase (RdRp) gene with 434 basepair product, resulted 24 samples determined as presumptive positive. Eight out of 24 presumptive positive samples by PCR were analyzed further by nucleotide sequencing and confirmed coronavirus positive. Phylogenetic tree analyses to the eight coronavirus confirmed-sequences were constructed with MEGA-6.0 . The conclusion was 24 out of 95 samples suggested as presumptive positive to Bat CoV. Eight out of 24 samples were analyzed further by nucleotide sequencing and have similarities in the kinship. Three samples had the 98% nucleotide identity to BatCoV from Indonesia and five samples were 85-88% nucleotide identity to BatCoV from Thailand.